A Practical Investigation of Brain-based Teaching Approach: Teaching English Speaking Skill to Nursing Students - Farzaneh Iranmanesh; Mehry Haddad Narafshan; Mohammad Golshan (Kerman University of Medical Sciences, 2023)
Background: Brain-based teaching approach as one of the outcomes of the recent trend in neuroeducation employs brain-based learning insights and strategies to induce efficient and accelerated learning.Objectives: This study aimed to investigate the effects of a brain-based language instruction model on nursing students' English-speaking skill.Methods: In this quantitative study with quasi-experimental design and pre-test/post-test format, a model of brain-based instruction for 64 students of Nursing (50 females and 14 males) was incorporated into a required general English course at Islamic Azad University of Kerman, Iran during the academic year 2021-2022.Results: Analysis of the independent sample t-tests and one-way ANCOVA indicated that the experimental group with intervention program of brain-based teaching approach considerably outperformed the control group in the pre-test and the posttest regarding speaking skill (P<0.01).Conclusion: Tracing the natural learning process in the brain, adopting compatible teaching methods, and assigning pedagogical tasks greatly facilitated understanding of the learners, learning materials, and teaching methods as well as improved the educational outcomes.